Arbitrary waveform AC line filtering applicable to hundreds of volts based on aqueous electrochemical capacitors - Mingmao Wu (Nature Portfolio, 2019)
AC to DC conversion is important for renewable power sources, and requires suitable filtering capacitors. Here the authors report a series-connected configuration of aqueous hybrid electrochemical capacitors for alternate current line filtering of arbitrary waveforms in wide frequency and voltage ranges.